Teachers’ Trajectory of Pedagogical and Practical Experiences Toward Developing an English Textbook - Nabila Shufaira Muammar; Yuliyanah Sain; Andi Rachmawati Syarif; Md. Hasan Ali; Syarif Amin; Abdul Halim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates how the process of developing a first English Language Teaching (ELT) textbook chapter influences teachers’ pedagogical and practical experiences, as well as the challenges they encounter during the process. Grounded in Teacher Cognition and Teacher Identity perspectives, the study adopts a qualitative approach to examine how teachers engage in instructional design for the first time. The findings reveal that textbook development pushes teachers to move beyond intuitive teaching toward more intentional and structured pedagogical design, where instructional decisions must be explicitly justified and aligned with learning objectives. This process activates and reorganizes teachers’ knowledge, beliefs, and prior experiences through continuous decision-making. At the same time, teachers face several challenges, including difficulties in translating pedagogical ideas into practical materials, contextualizing content to learners’ needs, and managing constraints such as time, curriculum demands, and workload. Rather than functioning as barriers, these challenges act as catalysts for professional growth, encouraging adaptive and context-sensitive decision-making. The study also highlights a parallel transformation in professional identity, as teachers shift from being material users to active designers and contributors. Overall, the findings suggest that textbook development serves as a critical site for teacher learning, where cognition, practice, and identity are dynamically interconnected, offering important implications for teacher education and professional development.